The problem of the protection of cultural identity during the new Media globalism Reading in Concepts, dimensions and new challen - Ben Laalam, Semhane; Benane, Karima (Journal of Social Sciences and Humanities, 2022)
This study aims at identifying the new challenges that are conffronted by the cultural identities during the new media globalism which becomes the main feature of this era through whith the concept of cultural identity and its boundaries have been changed and they are replaced by new concepts related to the new communication technology which creates new and various cultural concepts which distinguish the place from the identity and it overgoes the cultural, social and political characteristics of communication especially during the ownership and control of the west on communication technology that represents the main influencer on the world in an era overwhelmed by globalism and controlled by the information society and digital environment and embodies that values of the west culture in comparison with other cultural identities mainly the Islamic west culture. This study has used a descriptive and analytic method in order to study the problem of cultural identity during the new media globalism and this method is related to the study of the reality of events, phenomena and opinions and its, analysis and interpretation the thing that has incited as to reach these results that are considered as answers to the problem of our study .The study resulted to a set of important results and among these results, the one which relates the cultural identity during globalism to the technique that is the new communication technology which represents the main influencer and the doer .